Body fat percentagem and body mass index predispose chronic kidney disease patients to variations on blood biomarkers (Research, Society and Development, 2022)
Objective: To analyze variations of biomarkers with different body mass index (BMI) and body fat percentage (% BF). Methods: Cross-sectional study, comprising 173 patients with CKD. Twenty blood biomarkers were evaluated. BMI was categorized as eutrophic and overweight. % BF was assessed by air displacement plethysmography and rated high when ≥25% for men and ≥32% for women. Four groups were categorized: eutrophic (adequate BMI and % BF), normal-weight obese (adequate BMI and high % BF), overweight and adequate % BG (high BMI and normal % BF) and real obese (BMI and% BF high). Results: Compared to eutrophic individuals, the “normal-weight obese” registered lower hemoglobin (12.5 mg / dl) and hematocrit (37.0%), higher values for phosphorus (3.6 mg / dl), CRP (0.2 mg / dL) and fasting blood glucose (105.5 mg / dL). The “real obese” had lower creatinine (1.6 mg / dL) and higher triglycerides (159 mg / dL), CRP (0.3 mg / dL) and fasting glucose (101 mg/dL). The group “overweight and adequate% BF” showed higher triglycerides (217 mg / dL) blood glucose (108mg / dL) and lower HDL-c (33.9 mg / dL). Conclusions: The “obese of normal weight” showed more variations on the biomarkers. The “overweight and adequate% BF” and “real obese” groups had higher serum values for some parameters. The need to assess combined parameters is emphasized, as both BMI and% BF can influence biochemical markers.